Smart Roundabout Coordination Systems for Sustainable Urban Mobility - Halawani, Ahmed T. M. (Salehan Institute of Higher Education, 2025)
Traffic signal coordination control is a smart approach used in urban networks to relieve the congestion by increasing corridor throughput and minimizing overall traffic delay. Previous studies have investigated various signal coordination challenges; however, integrating roundabouts into a coordinated signalized corridor without compromising their operational distinctiveness remains underexplored. This study introduces an adaptive traffic signal offset strategy incorporating a platoon compaction factor to address the dispersion effects caused by roundabouts, ensuring the preservation of platoon movement along the coordinated corridor. The method was evaluated using the PTV VISSIM micro-simulation software. The results show improvements in sustainability indicators at roundabouts, with average corridor-level delays minimized by 17%, delays associated with vehicle stops reduced by 28%, fuel consumption reduced by 16%, and emissions reduced by 9% and 16% for NOₓ and CO₂, respectively. These improvements were statistically significant, affirming the robustness of the proposed method. The findings underscore the potential benefits of implementing this framework in real-world traffic scenarios, contributing to making urban transportation systems more efficient and sustainable. Doi: 10.28991/CEJ-2025-011-02-013 Full Text: PDF